Physiological, kinematic, and electromyographic responses to kinesiology-type patella tape in elite cyclists - Hébert-Losier, K.; Yin, N. S.; Beaven, C. M.; Chow, Tee, C. C. L.; Richards, J. (Journal of Electromyography and Kinesiology, 2019)
Kinesiology-type tape (KTT) has become popular in sports for injury prevention, rehabilitation, and performance enhancement. Many cyclists use patella KTT; however, its benefits remain unclear, especially in uninjured elite cyclists. We used an integrated approach to investigate acute physiological, kinematic, and electromyographic responses to patella KTT in twelve national-level male cyclists. Cyclists completed four, 4-minute submaximal efforts on an ergometer at 100 and 200?W with and without patella KTT. Economy, energy cost, oxygen cost, heart rate, efficiency, 3D kinematics, and lower-body electromyography signals were collected over the last minute of each effort. Comfort levels and perceived change in knee stability and performance with KTT were recorded.